Development as a battlefield / edited by Irene Bono, Béatrice Hibou. - Hibou, Béatrice; Bono, Irene (Brill Nijhoff, 2017)
"Development as a Battlefield' is an innovative exploration of the multidimensional meanings of -and interactions between- conflict and development. The two phenomena are all too often regarded as ostensibly antagonistic. This was exemplified again in the context of the Arab Spring that erupted in December 2010 and was eventually short-lived in several countries of the Middle-East and North-Africa (MENA) region. This volume, the 8th thematic issue of 'International Development Policy, is an invitation to reconsider and renew the way social scientists usually seek to make sense of socio-political and economic developments in the MENA region and beyond."--Foreword.
Keywords: Economic development -- Middle East.; Social conflict -- Middle East.; Economic development.; Social conflict.; Middle East.